2017
DOI: 10.3389/fpubh.2017.00233
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Clinical Decision Support Systems Promote Absolute Cardiovascular Risk Assessment: An Important Primary Prevention Measure in Aboriginal and Torres Strait Islander Primary Health Care

Abstract: BackgroundAboriginal and Torres Strait Islander Australians experience a greater burden of disease compared to non-Indigenous Australians. Around one-fifth of the health disparity is caused by cardiovascular disease (CVD). Despite the importance of absolute cardiovascular risk assessment (CVRA) as a screening and early intervention tool, few studies have reported its use within the Australian Indigenous primary health care (PHC) sector. This study utilizes data from a large-scale quality improvement program to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…A 2018 study using nationally representative data from the 2012–13 Australian Aboriginal and Torres Strait Islander Health Survey found that 1.1% of Aboriginal and Torres Strait Islander peoples aged 18–24 years (95% CI, 0.0–2.5%) and 4.7% Aboriginal and Torres Strait Islander peoples aged 25–34 years (95% CI, 2.0–7.5%) were at high absolute risk of having a primary CVD event in the next 5 years . These findings support those previously reported in specific Aboriginal and Torres Strait Islander populations . The proportion of people aged 25–34 years at high risk (4.7%) is similar to that seen in non‐Indigenous people aged 45–54 years (4.0%), the age from which absolute CVD risk assessment is recommended for this population under the current NVDPA guidelines .…”
Section: Recommendationsmentioning
confidence: 97%
“…A 2018 study using nationally representative data from the 2012–13 Australian Aboriginal and Torres Strait Islander Health Survey found that 1.1% of Aboriginal and Torres Strait Islander peoples aged 18–24 years (95% CI, 0.0–2.5%) and 4.7% Aboriginal and Torres Strait Islander peoples aged 25–34 years (95% CI, 2.0–7.5%) were at high absolute risk of having a primary CVD event in the next 5 years . These findings support those previously reported in specific Aboriginal and Torres Strait Islander populations . The proportion of people aged 25–34 years at high risk (4.7%) is similar to that seen in non‐Indigenous people aged 45–54 years (4.0%), the age from which absolute CVD risk assessment is recommended for this population under the current NVDPA guidelines .…”
Section: Recommendationsmentioning
confidence: 97%
“…Five articles met our inclusion criteria. Studies included Aboriginal and/or Torres Strait Islander people (age range 18-76 years) from the Northern Territory 7-10 , Queensland 10,11 , Western Australia 10 and South Australia. 10 Approximately equal numbers of men and women were included, and all studies were of fair or good quality.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies described absolute CVD risk profiles in Aboriginal and Torres Strait Islander communities. 9,10 High absolute CVD risk commenced at an early age, with approximately 6-9% of those aged 20-34 years having moderate (10-15% over 5 years) or high (>15% over 5 years) absolute CVD risk. 9,10 There was evidence that the Framingham Risk Equation underestimated CVD risk by around 1.5-2.5 times when used alone, without applying criteria for clinically determined high risk.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indigenous clients had four-fold higher odds of having a CVRA if they had received an Indigenous-specific health assessment (1388 client records from 48 Indigenous PHC centres in the Northern Territory, 2012-14) (Matthews et al 2017). Cardiovascular risk assessments are not directly specified in the MBS item 715 descriptor despite their recognised role in curbing the onset of cardiovascular disease.…”
Section: Lesson 1 Health Assessments Are Associated With Improved Qumentioning
confidence: 99%